Nanofluid based on activated hybrid of biomass carbon/graphene oxide: Synthesis, thermo-physical and electrical properties. (March 2016) - Yarmand, Hooman; Gharehkhani, Samira; Shirazi, Seyed Farid Seyed; Amiri, Ahmad; Montazer, Elham; Arzani, Hamed Khajeh; Sadri, Rad; Dahari, Mahidzal; Kazi, S.N.
Abstract: In the present study a mixture of empty fruit bunch (EFB) fiber as a matrix material and graphene oxide (GO) as a guest was activated by processing with KOH. The structural characterization was performed by various techniques such as field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD) and Raman. The as-synthesized hybrid containing activate carbon/graphene (ACG) was dispersed in ethylene glycol (EG) at various mass fractions in order to evaluate the thermo-physical and electrical properties such as thermal conductivity, electrical conductivity, viscosity, density and specific heat capacity of the suspensions at different temperatures. Thermal conductivity of ACG dispersed in EG based nanofluid shows an enhancement of 6.47% at 40 °C and weight fraction of 0.06%.